Perbandingan Hasil Block Adjustment Pada Bidang Tanah Menggunakan Plugin Perekat dan Plugin Adumanis Pada Quantum GIS - , Mohammad Rizki Nadiyanto; Indrianawati (Jurnal Serambi Engineering, 2025)
The PTSL program aims to accelerate land certification; however, spatial inconsistencies, such as gaps and overlaps between land parcels, are still frequently encountered. This study seeks to enhance the quality of spatial data using a block adjustment method based on ISO 19157:2013, utilizing the Adumanis and Perekat plugins in Quantum GIS. A comparative quantitative approach was adopted by analyzing changes in area and topological consistency across 2,197 land parcels and 1,310 control points in Mutisari Village, Watumalang District, Wonosobo Regency. The results indicate that the Perekat plugin is more effective in preserving parcel area, with only 0.96% of parcels exceeding the tolerance threshold, compared to 9.83% when using the Adumanis plugin. Regarding topological consistency, the Perekat plugin also outperforms Adumanis, with 94.76% of parcels free from spatial errors, while Adumanis achieved 92.17%. These findings demonstrate that the Perekat plugin delivers better spatial and topological accuracy in land parcel adjustments than the Adumanis plugin.